(untitled) (Bangladesh Journal of Botany, 2026)
Seaweeds contain a broad range of vitamins, particularly water-soluble vitamins. The objective of this study was to measure the levels of vitamin C and vitamin B6 in seaweed samples by acidic and enzymatic hydrolysis, followed by reverse-phase high-performance liquid chromatography (RP-HPLC) analysis using a UV detector. Vitamin C and vitamin B6 contents ranged from 1.62 to 48.28 mg/100 g and 3.54 to 22.24 mg/100 g, respectively. Sargassum sp. collected from Teknaf showed the highest vitamin C content, while Gracilaria sp. contained the highest level of vitamin B6. The vitamin levels varied depending on the seaweed species. However, this study revealed that seaweed can be a good source of vitamin C and vitamin B6. Therefore, it is possible to conclude that this seaweed has the potential to serve as an alternative source of vitamins for food security in Bangladesh. Bangladesh J. Bot. 55(1): 61-67, 2026 (March)